2008
DOI: 10.1002/bjs.6019
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection for colorectal cancer

Abstract: With experience, laparoscopic surgery is feasible in around 90 per cent of elective colorectal cancer resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 26 publications
2
49
1
3
Order By: Relevance
“…Nonetheless, within the obese group, there are patients who are undoubtedly more challenging. While some centres report laparoscopic completion rates of over 90% overall 15 we found a conversion rate of 16%, rising to 27% in the obese group using a strict definition of conversion as any incision larger than that required to extract the specimen. There was a statistically higher AFR in patients in the obese group who underwent conversion, but not a statistically significantly higher BMI.…”
Section: Discussioncontrasting
confidence: 56%
“…Nonetheless, within the obese group, there are patients who are undoubtedly more challenging. While some centres report laparoscopic completion rates of over 90% overall 15 we found a conversion rate of 16%, rising to 27% in the obese group using a strict definition of conversion as any incision larger than that required to extract the specimen. There was a statistically higher AFR in patients in the obese group who underwent conversion, but not a statistically significantly higher BMI.…”
Section: Discussioncontrasting
confidence: 56%
“…Colorectal cancer is presently the third most common malignancy in Korea, and the rate is still increasing [14]. The use of laparoscopic resection of colorectal cancer has also increased [15,16], including in Asian obese patients. Studies in Western populations have shown that obese patients undergoing laparoscopic colorectal surgery are at increased risk of conversion to an open procedure [1][2][3]17].…”
Section: Discussionmentioning
confidence: 99%
“…Amount of lymph nodes harvested ranged from 0 to 68, with average 12.27 ± 9.02, which had met the criteria of conventional open radical operation. In the study of Buchanan et al (2008), the number of lymph nodes harvested ranged from 0 to 24, with average 9, in which 135 patients had accepted conventional open surgery. The radical efficacy of laparoscopic colorectal operation is evaluated in terms of local recurrence, metastasis, wound plantation and long-term survival.…”
Section: Radical Efficacy Of Laparoscopic Colorectal Surgerymentioning
confidence: 99%